PENGEMBANGAN MULTIMEDIA PEMBELAJARAN MENGGUNAKAN KAHOOT PADA MATERI ASAM BASA BERBASIS PROBLEM BASED LEARNING BERORIENTASI MINAT BELAJAR MURID - Ayu Wiranti; Rayandra Asyhar; Epinur; Wilda Syahri; Firdiawan Ekaputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a Problem-Based Learning (PBL)-based multimedia learning tool using the Kahoot platform for acid-base topics, as well as to determine the feasibility of the tool and students’ responses to the developed product. This study employs the Research and Development (R&D) method using the Lee & Owens development model, which comprises five stages: analysis, design, development, implementation, and evaluation. The analysis stage was conducted through observation, teacher interviews, and the distribution of questionnaires to identify learning needs, student characteristics, and technological readiness. The design stage involved product design, including the preparation of materials, flowcharts, storyboards, and research instruments. The development stage involved the creation of a prototype, which was then validated by subject matter experts and media experts, evaluated by teachers, and revised based on feedback. The implementation stage involved a small-group pilot test with 9 twelfth-grade students. The evaluation stage aimed to assess the feasibility and practicality of the product. The data collected consists of qualitative and quantitative data obtained through interviews and questionnaires. Data analysis was performed descriptively using a Likert scale and percentages. The results of the study indicate that the educational multimedia developed falls into the “acceptable” category and has received a positive response from students, making it suitable for use as an interactive and innovative alternative learning medium.